Secular trends in body image dissatisfaction and associated factors among adolescents (2007–2017/2018) - Gonzaga I.* (2023)
© 2023 Gonzaga et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Objective To assess secular trends in body image dissatisfaction and associated factors among adolescents over a 10-year period (2007-2017/2018). Methods The sample included 1,479 (2007, n = 531; 2017/2018, n = 948) high school adolescents of both sexes, aged 14 to 18 years, of schools in a city in southern Brazil, in 2007 and 2017/ 2018. Data were collected on sex, age, physical activity (IPAQ, short form), anthropometric measurements (body weight, height, and triceps and subscapular skinfolds), and body image dissatisfaction (figure rating scale). The variables were compared with Independent samples t-test and Mann–Whitney U-test. The associations between sex and other variables were examined with chi-square test, and the factors associated with body image were identified with multinomial logistic regression. Results Most adolescents were dissatisfied with their body image in 2007 (65,2%) and 2017/2018 (71,1%). The prevalence of body dissatisfaction increased by 9.2% over the 10-year period, particularly dissatisfaction with thinness (21.3%). After stratification by sex, in 2017/2018 sample, dissatisfaction with overweight was 46.1% greater in boys, and dissatisfaction with thinness was 66.9% greater in girls. Factors found to be significantly associated with body image dissatisfaction were physical activity level, and body adiposity. Conclusions There was a secular trend toward increased body image dissatisfaction in both sexes. Future efforts should go beyond scientific production, in public and private environments aimed at increasing awareness of health issues related to body care in the physical, psychological, and environmental domains.